A low-cost fiber based displacement sensor for industrial applications - Siti Mahfuza Saimon; Nor Hafizah Ngajikin; Muhammad Shafiq Omar; Mohd Haniff Ibrahim; Muhammad Yusof Mohd Noor; Ahmad Sharmi Abdullah; Mohd Rashidi Salim (Universitas Ahmad Dahlan, 2019)
In this paper, a low-cost fiber optic displacement sensor (FODS) using a bundle of plastic optical fiber (POF) as a probe is developed and presented. The sensor consists of a high power light emitting diode (LED) as light source, a probe with multiple receiving plastic optical fiber and a photodiode detector. The sensor is characterized at millimeter distance and the sensor output is analyzed from 0 mm to 13 mm displacement. The sensitivity of the sensor is found to be 5.38 mV/mm over 2.6 mm sensing range. The sensor is very useful for close distance target since it is highly sensitive at the front slope. The low development cost, high degree of sensitivity and simplicity of the design make it suitable for wide range of industrial applications.